2023
DOI: 10.3389/fendo.2022.1057749
|View full text |Cite
|
Sign up to set email alerts
|

Is prolactin receptor signaling a target in dopamine-resistant prolactinomas?

Abstract: The hypothalamic neuroendocrine catecholamine dopamine regulates the lactotroph function, including prolactin (PRL) secretion, proliferation, and apoptosis. The treatment of PRL-secreting tumors, formerly known as prolactinomas, has relied mainly on this physiological characteristic, making dopamine agonists the first therapeutic alternative. Nevertheless, the group of patients that do not respond to this treatment has few therapeutical options. Prolactin is another physiological regulator of lactotroph functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…AKT1, as a member of AKT kinase, takes part in cellular progress, namely cell proliferation, apoptosis, and glucose metabolism. The PI3K/AKT pathway has formerly been reported to be connected with prolactinoma development (Dworakowska et al, 2009; Ferraris, 2022). It was shown that the PVE markedly suppressed the expression of AKT1 and Bcl-2/BAX protein.…”
Section: Discussionmentioning
confidence: 99%
“…AKT1, as a member of AKT kinase, takes part in cellular progress, namely cell proliferation, apoptosis, and glucose metabolism. The PI3K/AKT pathway has formerly been reported to be connected with prolactinoma development (Dworakowska et al, 2009; Ferraris, 2022). It was shown that the PVE markedly suppressed the expression of AKT1 and Bcl-2/BAX protein.…”
Section: Discussionmentioning
confidence: 99%